Condições de trabalho dos profissionais de enfermagem em hospitais no Brasil: revisão integrativa - Uchôa, Cristiane Costa (2023)
The health of healthcare workers has a close relationship with the conditions of work. Nursing is considered one of the occupations with the highest risks tension and illness. The study aimed to analyze the relationship between working conditions and health of nursing professionals in the hospital network in Brazil and characterize the research on this topic. It was a study of an integrative literature review with an online survey carried out in January 2023 on the Virtual Health Library (VHL) portal, in the Literature Databases Latin American and Caribbean Health Sciences (LILACS), Medical LiteratureAnalysisandRetrieval System Online (MEDLINE) and Database in Nursing (BDENF), available from 2017 to 2022, through the descriptors: Nursing Professionals; Work conditions; Hospitals in Brazil; Worker's health. From this research, studies were presented second title, year, authorship, country of publication and language, design, level of evidence, results and conclusions of the authors. The first search resulted in 148 articles and, after applying the inclusion and exclusion criteria, 20 articles resulted in the final sample. The working conditions of nurses working in hospitals in Brazil have been described as inadequate in terms of physical space, with long working hours and scarcity of inputs and human resources. Those aspects have a negative impact on the health of these professionals. Given this, the importance of studies on the work process of nurses, especially in precarious conditions, it is evident. It is essential that the institutions invest in improvements to preserve the functional capacity of professionals. This will result in improved patient care and will strengthen the recognition of nurses' work in the health sector